Effect of tert-Butylhydroquinone on the Oxidative Stability and Storage Quality of Tabak-Maz, a Kashmiri Meat Product - Dua, Sourab; Bhat, Z. F.; Kumar, Sunil (Journal of Meat Science, 2015)
The study was conducted to evaluate the effect of tert-Butylhydroquinone (TBHQ) on the oxidative stability and storage quality of Tabaq-Maz, a popular traditional meat product of Wazwan-the cuisine of indigenous meat products of Kashmir. The products were prepared and treated with TBHQ (200 ppm) and were aerobically packaged and assessed for lipid stability and storage quality parameters under refrigerated (4±10C) conditions. TBHQ showed a significant (p<0.05) effect on the lipid stability of the products as TBHQ treated products exhibited significantly (p<0.05) lower TBARS (mg malonaldehyde/kg) and FFA (% oleic acid) values for the entire period of storage. No significant (p>0.05) effect was observed on the microbiological characteristics of the products as TBHQ treated products showed comparable values with respect to control for total plate count, psychrophillic count and yeast and mould count throughout the period of storage. Sensory parameters showed significant (p<0.05) decreasing trend for both control as well as TBHQ treated products throughout the period of storage, however, significantly (p<0.05) higher scores were observed for treated products in comparison to control. Thus, it may be concluded that TBHQ successfully improved the lipid stability and storage quality of Tabak-Maz during refrigerated (4±10C) storage and may be commercially exploited as an antioxidant in Tabak-Maz.